Kajian Perubahan Nilai Konduktivitas Termal pada Bata Ringan dengan Penggunaan Crude Palm Oil (CPO) sebagai Bahan Penyimpan Kalor - Lia Laila; Asep Yunta Darma (JOURNAL OF APPLIED SCIENCE (JAPPS), 2020)
Indonesia is the largest producer of Crude Palm Oil (CPO) in the world. The use of CPO is mostly for edible oils and biofuels. Even though CPO potential is huge, the development of CPO in other forms is still limited. CPO has a melting point of 25˚C - 50˚C which is suitable to be develoved in the environment of Indonesia. This characteristic allows CPO to be used as phase change material. This study examines the use of CPO as a material to reduce the thermal conductivity of light bricks. The idea is to make the brick as a building material has the ability to maintain room conditions from fluctuative ambient temperatures. The results showed that the addition of effective CPO to reduce the thermal conductivity of light bricks was 2.5 to 7.5 ml per 160 cm3.